2018
DOI: 10.3390/agriculture8020020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elemental Sulfur as Fertilizer Ingredient on the Mobilization of Iron from the Iron Pools of a Calcareous Soil Cultivated with Durum Wheat and the Crop’s Iron and Sulfur Nutrition

Abstract: Abstract:The granules of conventional fertilizers have been enriched recently with 2% elemental sulfur (S 0 ) via a binding material of organic nature and such fertilizers are suitable for large scale agriculture. In a previous work, we demonstrated that a durum wheat crop that received the enriched fertilization scheme (FBS 0 -crop) accumulated a higher amount of Fe compared to the durum wheat crop fertilized by the corresponding conventional fertilization scheme (F-crop). In this study, we investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…We have found that a portion of the existing microorganisms in the rhizosphere presented arylsulfatase activity [30], thus releasing sulfate bound in the soil organic matter, the percentage of which increased with the addition of ES-enriched fertilizer. Moreover, the fertilization with FBES at sowing affected the iron fractions of the rhizosoil towards iron mobilization, thus providing more iron to the crop, which apart from the iron nutrition fortified the crop’s sulfur nutrition, too [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that a portion of the existing microorganisms in the rhizosphere presented arylsulfatase activity [30], thus releasing sulfate bound in the soil organic matter, the percentage of which increased with the addition of ES-enriched fertilizer. Moreover, the fertilization with FBES at sowing affected the iron fractions of the rhizosoil towards iron mobilization, thus providing more iron to the crop, which apart from the iron nutrition fortified the crop’s sulfur nutrition, too [14].…”
Section: Discussionmentioning
confidence: 99%
“…Soil fertility of each field was determined prior to crop establishment. In order to ensure comparable soil conditions between the corresponding F- and FBES-trials, each area was arbitrarily divided into plots 15 m × 7 m (105 square meters) each [14]. All perimetric plots were excluded, while the internal plots were grouped into five successive groups.…”
Section: Methodsmentioning
confidence: 99%
“…A research article contributed to this special issue by Bouranis et al [14] addresses interactions between various nutrients and forms of nutrients with special reference to elemental sulfur and to iron in calcareous soils. Iron nutrition of crops can be improved by the addition of elemental sulfur to a standard fertilizer mixture.…”
Section: Nutrient Availability and Acquisitionmentioning
confidence: 99%
“…Briefly, the FBS 0 fertilizer used in this experiment contained sulfate as the accompanying anion of ammonium (i.e., directly available S), along with 2% S 0 (not directly available S). The ingredients of the binder (i.e., a mixture of molasses and glycerol) are both water-soluble and can be used by soil microorganisms, along with S 0 , thus suggesting microbial action around the granules [26,27]. In this paper we show that the aforementioned interactions are highly affected by the rhizospheric microbiome under the circumstances.…”
Section: Discussionmentioning
confidence: 87%
“…The application of fertilizer granules with incorporated elemental sulfur (FBS 0 ) in durum wheat crop produced a higher yield and higher S and Fe contents compared with the application of the conventional (F) ones, provided that the experimental fields (F and FBS 0 ) were of comparable quality. The fertilization with FBS 0 at sowing mobilized iron from the rhizosoil, thus providing more iron to the crop; in addition, it boosted the crop’s sulfur content [26]. On the other hand, the level of available phosphorus was found to be correlated with the corresponding relative change in the yields (YFBS 0 /YF), presenting a strong positive relationship, and the content of 8 mg kg −1 was a turning point; lower values resulted in a lower yield compared with the conventional crop [27].…”
Section: Introductionmentioning
confidence: 99%